2016
DOI: 10.1037/cou0000108
|View full text |Cite
|
Sign up to set email alerts
|

Does self-stigma reduce the probability of seeking mental health information?

Abstract: An important first step in seeking counseling may involve obtaining information about mental health concerns and treatment options. Researchers have suggested that some people may avoid such information because it is too threatening due to self-stigma and negative attitudes, but the link to actual help-seeking decisions has not been tested. Therefore, the purpose of the present study was to examine whether self-stigma and attitudes negatively impact decisions to seek information about mental health concerns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 40 publications
6
124
0
1
Order By: Relevance
“…Previous studies have found that self-stigma is associated with negative attitudes towards treatment-seeking and negatively impacts the decision to seek information and help [13, 39, 40]. The attachment of self-stigma to developing identity in emerging adults may be of particular importance as this is the life-stage where individuals become more concerned with questions surrounding their identity and how they fit in [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that self-stigma is associated with negative attitudes towards treatment-seeking and negatively impacts the decision to seek information and help [13, 39, 40]. The attachment of self-stigma to developing identity in emerging adults may be of particular importance as this is the life-stage where individuals become more concerned with questions surrounding their identity and how they fit in [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Stigma significantly predicts likelihood of seeking mental health services, with higher self-stigma associated with fewer services sought (Lannin et al, 2016). Men are more likely than women to be reluctant about entering in-person couple therapy (Doss, Atkins, & Christensen, 2003).…”
Section: Importance Of Technology For Family and Couple Interventionsmentioning
confidence: 99%
“…Among 583 college students, most of whom identified as European-American (86%), Vogel, Wade, and Haake (2006) found levels of self-stigma associated with seeking mental health care predicted less intention to seek treatment, beyond the effects of public stigma and anticipated risks and benefits. Similar results were reported in more recent research (Lannin et al, 2016) that indicated that even the decision to seek information about counseling, such as that available online, was associated with levels of self-stigma. Lannin et al (2016) found among a sample of undergraduate college students at a large Midwestern university (N = 370) that selfstigma of mental illness was significantly associated with decreased probability of seeking counseling information and online mental health information.…”
Section: Self-stigma or Internalized Stigmasupporting
confidence: 77%
“…Similar results were reported in more recent research (Lannin et al, 2016) that indicated that even the decision to seek information about counseling, such as that available online, was associated with levels of self-stigma. Lannin et al (2016) found among a sample of undergraduate college students at a large Midwestern university (N = 370) that selfstigma of mental illness was significantly associated with decreased probability of seeking counseling information and online mental health information. In addition, findings indicated that self-stigma was a significant predictor of negative attitudes toward counseling.…”
Section: Self-stigma or Internalized Stigmasupporting
confidence: 77%
See 1 more Smart Citation